Electrospun Biocarriers with Immobilized Yeasts for Eco-Friendly Biocontrol of Fusarium graminearum - Petya Tsekova; Mariana Petkova; Mariya Spasova; Olya Stoilova (Agronomy)
This study reports, for the first time, the successful application of chitosan oligosaccharide (COS) and 2-hydroxyethyl cellulose (HEC) coatings on electrospun poly(3-hydroxybutyrate) (PHB) materials for the immobilization of non-conventional yeast strains with fungal biocontrol potential. The coatings enhanced the surface wettability of PHB fibers, facilitating efficient yeast adhesion and viability maintenance. Among the tested strains, Pichia acaciae YD6 was newly isolated and characterized, while Pichia fermentans YP6 and Zygosaccharomyces bailii YE1 had previously been identified as endophytic colonizers. All three strains demonstrated high adaptability, efficient immobilization, and antagonistic activity, confirming their potential for biocontrol applications. COS-coated PHB fibers promoted greater colony expansion than those coated with HEC. Antifungal assays of the yeast-containing biocarriers showed significant inhibition of F. graminearum growth. These findings underscore the potential of PHB-based fibrous materials as sustainable, bioactive carriers for yeast immobilization, with desirable biological properties. This approach offers a promising and eco-friendly strategy for pest control and bioactive agent delivery in agricultural applications.